Persepsi karyawan terhadap sistem pelatihan di the patra bali resort & villas - Hamdani, Ahmad; Suarka, Fanny Maharani; Sari, Ni Putu Ratna (Jurnal Kepariwisataan dan Hospitalitas, 2019)
The Patra Bali is one of the state-owned enterprises, under of PT. Patra Jasa. Therefore PT. Patra Jasa has its own training time standard. The Patra Bali management must have a training system to achieve the target set training time. The purpose of this study was to find out application of the training system at The Patra Bali Resort & Villas, in addition to teformine the responses of employees toward the training system that runs at The Patra Bali Resort & Villas. Methods of data collection is done by observation, interview, questionnaire and documentation. The technique of determining the sample using proporsionate stratified random sampling technique and obtained a sample of 100 people, and data analysis techniques used in research is descriptive qualitative. The results obtained in this study is the training system implemented at The Patra Bali Resort & Villas has formed a training cycle. In addition from the recapitulation results can be concluded that from some questions given can show that employee response shows the response with the lowest points are on the indicator of participants where the points earned over 4.1 points. While for the highest point is on the indicator of the determination of the coach that is equal to 4.47 points. Key Words           : System Training, Perception Employees, The Patra Bali Resort & Villas